Competition in the production of electronic microchips (semiconductors) as an issue in US – China relations - Salloum, Feras Sadiq (Journal of the Belarusian State University. International Relations, 2023)
Wars and battles throughout the 20th century were fought mostly over oil in resource-rich nations. Recently, the world’s two biggest economies, China and the United States, clashed over electronic microchips, a crucial component of almost every modern electronic device. As we describe the semiconductor sector as an area of intensifying technological competition between the US and China, we look at each party’s measures against their rival and examine what they did to minimise the side effects of these measures. We conclude that the confrontation in the semiconductor sector typifies the fight for economic and technical dominance that will shape global politics in the 21st century. We also predict that in this ongoing confrontation, Taiwan will shortly come to the centre stage.
Keywords: electronic chips; United States; People’s Republic of China; Taiwan; sanctions; trade war